Organophosphate Hydrolase Is a Lipoprotein and Interacts with P(i)-specific Transport System to Facilitate Growth of Brevundimonas diminuta Using OP Insecticide as Source of Phosphate - Parthasarathy, Sunil (J Biol Chem, 2016)
Organophosphate hydrolase (OPH), encoded by the organophosphate degradation (opd) island, hydrolyzes the triester bond found in a variety of organophosphate insecticides and nerve agents. OPH is targeted to the inner membrane of Brevundimonas diminuta in a pre-folded conformation by the twin arginine transport (Tat) pathway. The OPH signal peptide contains an invariant cysteine residue at the junction of the signal peptidase (Spase) cleavage site along with a well conserved lipobox motif. Treatment of cells producing native OPH with the signal peptidase II inhibitor globomycin resulted in accumulation of most of the pre-OPH in the cytoplasm with negligible processed OPH detected in the membrane. Substitution of the conserved lipobox cysteine to serine resulted in release of OPH into the periplasm, confirming that OPH is a lipoprotein. Analysis of purified OPH revealed that it was modified with the fatty acids palmitate and stearate. Membrane-bound OPH was shown to interact with the outer membrane efflux protein TolC and with PstS, the periplasmic component of the ABC transporter complex (PstSACB) involved in phosphate transport. Interaction of OPH with PstS appears to facilitate transport of P(i) generated from organophosphates due to the combined action of OPH and periplasmically located phosphatases. Consistent with this model, opd null mutants of B. diminuta failed to grow using the organophosphate insecticide methyl parathion as sole source of phosphate.